Principal management in improving teacher performance and education quality in private vocational schools - Mochammad Irfan Fauzi; Eva Dianawati Wasliman (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
The role of school principals in leading educational institutions has a substantial influence on teacher performance and student learning outcomes, particularly in private vocational high schools. This study aims to explore how principals apply managerial strategies to enhance teacher professionalism and overall educational quality at SMK As-Sulaimaniyyah and SMK AMS Siliwangi in Cianjur Regency. A qualitative descriptive approach with a case study method was employed. Data collection involved direct observation, in-depth interviews, and document analysis, with the framework based on George R. Terry’s four core management functions: planning, organizing, actuating, and controlling. The findings indicate that both principals have implemented these management functions effectively, supported by leadership that is inspirational, participatory, and responsive to change. The development of a positive work culture, consistent professional development for teachers, and the integration of technology have contributed to creating a more effective learning environment. Regular evaluations and collaboration with external stakeholders further strengthen quality improvement efforts. In conclusion, structured and communicative leadership practices significantly contribute to improving teacher performance and educational standards in private vocational school settings.